GENERASI PENERUS BERKUALITAS DALAM PERSPEKTIF AL-QUR’AN - Ebing Karmiza (STAI Bumi Silampari, 2019)
Nearing the end of time more and more bad influences that could undermine Muslims to Muslims must strengthen and prepare generations of the best qualified and Muslims should study the Qur’an to know what that meant quality generation according to the Qur’an. The purpose of this study to find out how qualified generation in the Qur'an and its role. This research was library research or literature, with descriptive qualitative method.Qualified generation in the Qur'an is the next generation of people who have spiritual intelligence practice religious values are strong, have intellectual skills that can sustain and build for the future.